Business Transformation Analysis at PT. Industrial Estate of Makassar - Muhammad Mahmud; Muhammad Asdar; Yunus Amar (Hasanuddin Journal of Business Strategy, 2021)
This study aims to determine the general industrial estate business model and analyze the key factors in formulating the best strategy for industrial estate development. In addition, this study also aims to conduct comparative research related to the current business model of PT Industrial Estate of Makassar (KIMA) on the transformation and development of the proposed business. In the context of development, industrial estates have become a hallmark of an industrialization process and are considered a powerful tool for job creation, economic growth, and competitiveness. Along with technological advances, the needs and demands for improving the quality of services from tenants for logistics facilities, energy, water availability, hazardous waste treatment, comfort, and environmental safety in industrial estates have also increased–PT KIMA, previously as Landlord by selling/buying land and warehousing leases must develop as a service provider that supports the smooth running of industrial activities carried out by tenants. This study uses a descriptive method with a qualitative approach where the company’s data and information are the sources of primary data and the other sources as secondary data to ensure data triangulation is carried out in order to increase the validity of this study. This study finds that business transformation is absolutely necessary to ensure PT KIMA's businesses sustainability. Without that, PT KIMA will find it difficult to maintain and develop its business. Providing services to support tenants ‘daily business will increase their satisfaction, ensure their loyalty, and in the long term can attract new potential investors.